Struktura tekmovalne uspešnosti smucarjev skakalcev in skakalk drugega skoka na mali skakalnici na olimijskih igrah v beijingu leta 2022 - Jošt, B.; Vodicar, J.; Pustovrh, J. (Kinesiologia Slovenica, 2024)
The purpose of the research study was to determine the structure of the competitive performance variables of male and female ski jumpers who participated in the second series of the competition on the smaller HS106m ski jumping hill at the Beijing 2022 Winter Olympics. The dependent criterion variable was the length of the jump. The following independent variables were included: in-run velocity, flight velocity at a point 30 m after the end of the take-off table, velocity of movement of the jumper at landing, V-angle between the skis at a point 30 m after the end of the take-off table and wind speed. Descriptive statistics, correlation analysis, and factor analysis were used to analyze the data. Differences in the dependent criterion variable (jump length) were much higher in women (M = 85 m, SD = 8.3 m) than in men (M = 98 m, SD = 3.9 m). At a fairly similar in-run velocity, men achieved an average of 13 m longer final jump than women. A statistically significant correlation between jump length and wind speed was observed in males (r = .42). In females, the variables in-run velocity (r = .59) and landing speed (r = .59) were significantly corelated with jump length. The multiple correlation showed a much higher correlation of independent variables in women (Mult R = .78; Sig R = 0.00) than in men (Mult R = .54; Sig R = 0.23). The overall competitive performance factor for men and women was largely determined by the jump length and style scores variables. The wind speed factor was completely independent of the other independent variables. The research showed a significant difference in the average quality level of competitive performance in male and female category. In particular, women had a much higher variability in competitive performance than men. The results of the survey confirmed that for a top achievement, in addition to the length of the jump, the score for style is also important. Based on this important knowledge for practice, coaches should pay more attention to the development of the aesthetic component of ski jumping technique.